Factors influencing impulse buying of sports team merchandise in developing country: An empirical investigation - Mehrukh Salman; Shamila Khan; Mohammad Saif Aly Gul (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
Impulse buying is an immediate urge to make a purchase. Sports enthusiast tends to engage in impulse buying when it comes to sports team merchandise. The paper attempts to investigate what factors lead to impulse buying of sports team merchandise. AMOS was used to compute the variables for Structural Equation Modeling (SEM), using the data collected from 288 young sports enthusiasts belonging to the age bracket of 18-26. The results strongly support the claim that shopping enjoyment is not directly related to impulse buying but has pathways that lead to it. The research empirically shows that sports enthusiasts do indulge in impulse buying where money availability, in store display/marketing efforts and fan identification are promoting factors to shopping enjoyment and thus causing impulse buying.
Keywords: 330; impulse buying; sports merchandise; shopping enjoyment; marketing effort; money availability; fan identification